Dyarrheal Syndrome in a Patient Co-Infected with Leishmania infantum and Schistosoma mansoni - Gláucia Fernandes Cota; Luciana Inácia Gomes; Bruna Fernandes Pinto; Joanna R. Santos-Oliveira; Alda Maria Da-Cruz; Moisés Salgado Pedrosa; Wagner Luiz Tafuri; Ana Rabello (Case Reports in Medicine)
This case report describes an atypical clinical presentation of visceral leishmaniasis affecting the digestive tract and causing malabsorption syndrome in a patient without recognized immunosuppressive condition. After appropriate treatment for the classical visceral form of the disease, diarrhea persisted as the main symptom and massive infection by Leishmania was detected by histopathology analysis of the duodenal mucosa. Schistosoma mansoni coinfection was also confirmed and treated without impact on diarrhea. New course of amphotericin B finally led to complete improvement of diarrhea. Atypical visceral leishmaniasis involving the gastrointestinal tract is well recognized in HIV coinfection but very rare in immunocompetent patients. The factors determining the control or evolution of the Leishmania infection have not been completely identified. This case stresses the importance of atypical symptoms and the unusual location of visceral leishmaniasis, not only in immunodepressed patients, and raises the possible influence of chronic infection by S. mansoni reducing the immune response to Leishmania.